Pengaruh ball milling pada dispersi padat ibuprofen dengan pembawa HPMC terhadap ukuran partikel dan kecepatan disolusi kapsul - Nining, Nining; Gusmayadi, Inding; Romansyah, Febri (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2024)
One factor that greatly influences the active drug solubility is particle size. Ibuprofen is a non-steroidal anti-inflammatory that is poorly water-soluble, potentially slowing its drug dissolution. Milling is one way to reduce particle size and help to enhance drug dissolution. This research aims to study the milling process effect on the particle size of ibuprofen and the capsule dissolution rate. Micrometer-sized ibuprofen (P1) is processed to nanometer size using the wet-milling method for 15 hours (P2) and 20 hours (P3) using HPMC (Hydroxy Propyl Methyl Cellulose) as a stabilising polymer. All particles were evaluated for particle size, and FTIR was tested and formulated into capsules. The powder mass was evaluated for flow properties. Capsule evaluation was also carried out, which included a disintegration time test, weight uniformity test, and dissolution test. The three particles have sizes of 40.6 µm (P1), 438.9 ± 20.9 nm (P2), and 267.1 ± 4.1 nm (P3). FTIR test results show compatibility between ibuprofen and HPMC. The disintegration time test results and capsule weight uniformity met the compendial requirements. Based on the dissolution test, the three formulas showed significant differences (sig p 0.0002 < 0.05) in the per cent dissolution. Obtained Q60 F1-F3 respectively were 99.61 ± 8.75%; 110.03±5.97%; and 115.95 ± 3.34%. The conclusion obtained is that the milling process has a significant effect on the dissolution percentage of ibuprofen.